Pengembangan Bahan Ajar Menulis Deskripsi Menggunakan Model Circuit Learning pada Siswa Kelas VII SMP di Samarinda - Rakhmad Syarif; M. Bahri Arifin; Mohammad Siddik (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
Research on the development of teaching materials for writing descriptions using the learning model of Circuit learning needs to be done because teachers and students have difficulty learning the process of writing descriptions. This study aims (1) to find out the process of developing teaching materials in writing descriptions by using the Circuit Learning model (2) to measure the quality of teaching materials writing descriptions using circuit learning methods assessed from the validity and effectiveness. This study applies research and development methods conducted at Nabil Husen Middle School Samarinda. The results of development research can be seen from the validation results, namely material validation with a value of 88, graphic validation with a value of 86 and a validation of language values ​​with a value of 97 with very valid criteria. The effectiveness test results seen from the implementation of the lesson plan, the teacher's response value 93, the students' response value 93 and the value of the description writing test results obtained an average value of 88 with very effective criteria. Thus, the research development of teaching material writing descriptions by using the learning model of circuit learning in class VII students is very valid and effective.